Rnf220 is Implicated in the Dorsoventral Patterning of the Hindbrain Neural Tube in Mice - Wang, Yu-Bing; Song, Ning-Ning; Zhang, Lei; Ma, Pengcheng; Chen, Jia-Yin; Huang, Ying; Hu, Ling; Mao, Bingyu; Ding, Yu-Qiang (Frontiers in Cell and Developmental Biology, 2022)
Rnf220 has been reported to regulate the patterning of the ventral spinal neural tube in mouse. The brainstem has divergent connections with peripheral and central targets and contains unique internal neuronal groups, but the role of Rnf220 in the early development of the hindbrain has not been explored. In this study, Nestin-Cre-mediated conditional knockout (Rnf220Nestin CKO) mice were used to examine if Rnf220 is involved in the early morphogenesis of the hindbrain. Rnf220 showed restricted expression in the ventral half of ventricular zone (VZ) of the hindbrain at embryonic day (E) 10.5, and as development progressed, Rnf220-expressing cells were also present in the mantle zone outside the VZ at E12.5. In Rnf220Nestin CKO embryos, alterations of progenitor domains in the ventral VZ were observed at E10.5. There were significant reductions of the p1 and p2 domains shown by expression of Dbx1, Olig2 and Nkx6.1, accompanied by a ventral expansion of Dbx1+ p0 domain and a dorsal expansion of Nkx2.2+ p3 domain. Different from the case in the spinal cord, the Olig2+ pMN (progenitors of somatic motor neuron) domain shifted and expanded dorsally. Notably, the total range of the ventral VZ, and gene expression in the dorsal tube were unchanged. In addition, the post-mitotic cells derived from their corresponding progenitor domain including oligodendrocyte precursor cells (OPCs) and serotonergic neurons (5-HTNs) were also changed in the same trend as the progenitor domains do in the CKO embryos at E12.5. In summary, our data suggested similar roles of Rnf220 in the hindbrain dorsoventral (DV) patterning as in the spinal cord, with different effects on the pMN domain. Our work also revealed novel roles of Rnf220 in the development of 5-HTNs and OPCs.